1988
DOI: 10.1084/jem.167.3.1016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of functional lymphocytes in some (leaky) scid mice.

Abstract: Lymphoid and myeloid cells represent distinct lineages of a common hematopoietic stem cell (1-3). This distinction is dramatically illustrated in the autosomal recessive mouse mutant, scid . t Mice homozygous for the scid mutation (scid mice) are severely deficient in B and T lymphocytes whereas other hematopoietic cell types such as erythrocytes, monocytes, granulocytes, and megakaryocytes (all members of the myeloid series) are present in normal number (4, 5). Although the scid mutation appears to affect onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(148 citation statements)
references
References 36 publications
3
141
0
Order By: Relevance
“…In addition, inflammatory cells were seen accumulating both within lymphatics (E) and in the perilymphatic adipose tissue (F) . Since scid mice lack functional T and B cells (12)(13)(14) and since eosinophilia is dependent on cytokines produced by T cells, two very striking features of this inflammatory infiltrate are the absence of lymphocytes and eosinophils .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, inflammatory cells were seen accumulating both within lymphatics (E) and in the perilymphatic adipose tissue (F) . Since scid mice lack functional T and B cells (12)(13)(14) and since eosinophilia is dependent on cytokines produced by T cells, two very striking features of this inflammatory infiltrate are the absence of lymphocytes and eosinophils .…”
Section: Resultsmentioning
confidence: 99%
“…The scid mouse, which lacks functional T and B lymphocytes (12)(13)(14), readily allows the growth and differentiation of infective B. malayi larvae into mature adults, which mate and produce m£ This model should allow the future investigation into the interaction of the murine and human (15,16) immune system with the lymphatic filarial parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a mutation localized on mouse chromosome 16, presumed to affect an enzyme involved in DNA-splicing, these mice are unable to rearrange the genes coding for the antigen receptors of both T and B lymphocytes [2]. Although some scid mice become 'leaky' with increasing age [3], they do not develop a fully functional immune defence, as the mature T and B cells that do develop are low in numbers and oligoclonal [3]. These scid mice accept engrafted human tumours and other tissues as readily as the classical nude (athymic) mouse, and in some cases even better [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, functional antigen receptor rearrangements do occur through 'illegitimate' recombination [5]. A few T and B lymphocyte clones survive and can expand in vivo after exposure to antigens [6]. This phenomenon, that was referred to as 'leakiness' by Bosma et al, is observed in about 15% of young SCID mice, and increases in frequency with age and environmental exposure, especially in mice that are not kept under strict aseptic conditions [6].…”
Section: Scid Micementioning
confidence: 99%